Actinomycosis in Iran: Short Narrative Review Article. - Sadegh Khodavaisy; Ensieh Zibafar; Seyed Jamal Hashemi; Hanar Narenji; Roshanak Daie Ghazvini (Tehran University of Medical Sciences, 2014)
Actinomycosis is an indolent, slowly progressive infection caused by anaerobic or microaerophilic bacteria, primarily of genus Actinomyces, which colonize the mouth, colon and vagina. Mucosal disruption may lead to infection virtually at any sites in the body. The aim of this study was to underline different features of actinomycosis and to represent total data about etiologic agents, clinical, diagnostic and therapeutic approaches these infections. From a total of 38 case reports or series, ninety one cases were obtained by using of relevant articles reported as recorded cases in Iran (1972 to 2012). Analyzed data represented 21 cases of oral-servicofacial (23.1%), 7 cases of thoracic (7.7%), 17 cases of abdominal (18.7%), 21 cases of disseminated forms (23.1%) and 25 cases of others (27.5%). Findings indicated more common of these infections in men (61.5%). Actinomyces naeslundii (21 cases) was found as the most common causative agents in comparison with A. Israeli (15 cases), A. viscosus (3 cases) and A. bovis (1 case). The most patients had been successfully treated with penicillin although some cases needed surgery along with antibiotic therapy. Since some clinical features of actinomycosis are similar to malignancies, so the differential diagnosis of invasive forms must be considered. This report emphasizes on the importance of differential diagnosis of actinomycosis from similar diseases by clinicians.